2000
DOI: 10.1021/jm000079i
|View full text |Cite
|
Sign up to set email alerts
|

Novel Radiotracers for Imaging the Serotonin Transporter by Positron Emission Tomography:  Synthesis, Radiosynthesis, and in Vitro and ex Vivo Evaluation of 11C-Labeled 2-(Phenylthio)araalkylamines

Abstract: A series of four 2-(phenylthio)araalkylamines have been radiolabeled with 11 C and evaluated as potential radiotracers for imaging the serotonin transporter (SERT) by positron emission tomography (PET). All four candidates display high affinity for SERT and low affinity for the dopamine or norepinephrine transporters using in vitro binding assays. Biodistribution studies in rats demonstrated that tail-vein injection of the 11 C-labeled radiotracers resulted in high brain uptake of radioactivity with a preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
141
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 228 publications
(148 citation statements)
references
References 23 publications
7
141
0
Order By: Relevance
“…Synthesis of [ 11 C]DASB has been described previously (Ginovart et al, 2001;Wilson et al, 2000). Briefly, […”
Section: Scanningmentioning
confidence: 99%
“…Synthesis of [ 11 C]DASB has been described previously (Ginovart et al, 2001;Wilson et al, 2000). Briefly, […”
Section: Scanningmentioning
confidence: 99%
“…Especially, increased serotonin level in prefrontal cortex is thought to be a key step in the therapeutic mechanism of SSRIs (Bel and Artigas, 1992;Invernizzi et al, 1992Invernizzi et al, , 1996. Positron emission tomography (PET) studies with [ 11 C]-3-amino-4-(2-dimethylaminomethyl-phenylsulfanyl)benzonitrile ([ 11 C]DASB; Wilson et al, 2000) have shown that 80% occupancy of SERT by SSRIs is needed for the improvement of depression symptom (Meyer et al, 2001(Meyer et al, , 2004Suhara et al, 2003). However, only one-third of patients show significant mood improvement in response to an initial antidepressant treatment (Trivedi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in baboons (Szabo et al, 2002) and humans (Frankle et al, 2004;Houle et al, 2000;Meyer et al, 2001;Wilson et al, 2000) have demonstrated the suitability of a new SERT ligand, [ 11 C]DASB, for studying serotonin neurons in the living brain. [ 11 C]DASB appears to have two critical advantages over [ 11 C]McN5652, including a greater specific-to-nonspecific equilibrium activity ratio, and a measurable plasma-free fraction for use in tracer modeling (Frankle et al, 2004).…”
Section: Introductionmentioning
confidence: 99%